Apportionment Approach for Just-In-Time Sequencing Problem - Dhamala, Tanka Nath; Thapa, Gyan Bahadur (Journal of the Institute of Engineering, 2009)
The Just-in-Time sequencing of different products is a well-known socio-industrial problem which is supposed to minimize the maximum and total deviations between actual and ideal productions; and the apportionment problem is a socio-political problem which aims to allocate representatives to a state as close as its exact quota. Significant amounts of research have been done in these two problems independently. The relation between them has been studied from last decade. In this article, both problems are addressed with some just-in-time sequencing algorithms and their characterizations via apportionment. Key words: apportionment, divisor methods, algorithms, Just-in-Time sequencing. Journal of the Institute of Engineering, Vol. 7, No. 1, July, 2009 pp.76-89 doi: 10.3126/jie.v7i1.2065